Attitudes and Teacher Efficacy among Italian and Austrian Teachers: a Comparative Study - Petra Hecht; Paola Aiello; Erika Marie Pace; Maurizio Sibilio (Pensa MultiMedia, 2017)
The need to face complexity in today's school contexts requires the identification of variables that influence teacher agency and which contribute to the success of inclusion. To this aim an exploratory and comparative research was conducted with the goal of investigating attitudes towards inclusion and the perceptions of efficacy of 364 student-teachers, 221 of which were Italian whereas 143 were Austrian, following a teacher education course. Furthermore, the comparative study aided in shedding light on how factors such as the educational system and culture can influence the variables considered. Results show that in both groups attitudes and teacher efficacy are both above the mean, yet the Italian sample had higher scores. Within an ecological perspective, this could be also due to factors related to context and cultural dimensions. This research is part of a wider project involving a network of researchers investigating such variables through the use of scales that have been specifically designed to measure some predictive determinants of success of inclusion.